Breastfeeding as an Ideological Practice: Chinese Immigrant Mothers’ Postpartum Learning in Canada - Zhu, Yidan (Canadian Journal for the Study of Adult Education, 2017)
This paper problematizes Canadian breastfeeding policies and programs. It criticizes Canadian federal and provincial government policies and programs, which focus on a global goal of enabling all women to practise exclusive breastfeeding and do not pay enough attention to immigrant mothers’ breastfeeding experience. Based on an analysis of government policies and in‑depth qualitative interviews with two Chinese immigrant mothers in Canada, I argue that breastfeeding is an ideological practice associated with neo‑liberalized restructuring that shapes the organization of current breastfeeding policies, educational and medical programs, and migrant mothers’ everyday practice.